Precursor and Reactivity Development for the Deposition of Main Group Element and Group 4 Metal Oxide Thin Films - Al Hareri, Majeda (My University, 2023)
Atomic layer deposition (ALD) is a technique by which surface-based reactions between a precursor molecule (often metal-containing) and a co-reactant (e.g. H2O, O2 or H2) yield highly uniform and conformal (ultra-)thin films. The precursor and co-reactant are each delivered in the gas phase, separated from one another by inert gas purge steps. The self-limiting nature of these surface-based reactions allows the thickness of the film to be controlled solely by the number of ‘precursor – purge – co-reactant – purge’ cycles. This nano-scale control of film thickness allows for a large number of applications such as in flat panel displays, fuel and solar cells, and microelectronic devices. The first goal of this project was the pursuit of new low-temperature methods for main group elemental ALD using silyl-substituted precursor molecules. The second goal of the project was the development of alternative methods for thin film deposition of group 4 (M = Hf, Zr) oxides that would encourage effective (ie. void-free) filling of narrow (<20 nm) trenches in high-aspect-ratio (HAR) substrates. This thesis includes the development of new precursor molecules and reaction pathways, evaluation of precursor molecular structures, thermal stability, volatility and solution reactivity, identification of appropriate experimental conditions for ALD, and characterization of the resulting thin films. ALD of elemental antimony was achieved on hydrogen-terminated silicon (H-Si) and SiO2/Si substrates using Sb(SiMe3)3 (2-1) and SbCl3 in the temperature range 23- 65 °C. The mirror-like films were confirmed to be composed of crystalline antimony by XPS (for the film deposited at 35 °C) and XRD, with low impurity levels and strong preferential orientation of crystal growth relative to the substrate surface. To the best ofour knowledge, this is the first example of room temperature thermal ALD (with demonstrated self-limiting growth) of a pure element. Film growth at 35 °C exhibited a substrate-enhanced mechanism, characterized by faster film growth for the first ~125 ALD cycles, where substantial deposition is occurring on the original substrate surface (GPC (growth-per-cycle) = 1.3 Å on SiO2/Si, and 1.0 Å on H-Si), and slower film growth (GPC = 0.40 Å on SiO2/Si, and 0.27 Å on H-Si) after ~125 cycles, once much of the initial substrate surface has been covered. Films deposited using 500-2000 ALD cycles were shown to be continuous by SEM. The use of less than 250 cycles afforded discontinuous films. However, in this initial growth phase, when deposition is occurring primarily on the original substrate surface, in-situ surface pre-treatment by Sb(SiMe3)3 or SbCl3 (50 x 0.4 or 0.8 s pulses), followed by the use of longer precursor pulses (0.4 or 0.8 s) during the first 50 ALD cycles resulted in improved nucleation. For example, on H-Si, a continuous 6.7 nm thick film was produced after initial pre-treatment with 50 x 0.8 s pulses of SbCl3, followed by 50 ALD cycles using 0.8 s pulses. The use of longer ALD pulses in the first 50 ALD cycles following surface pre-treatment is likely required in order to achieve complete reactivity with an increased density of reactive surface sites. Boranes featuring bulky silyl or sterically unencumbered trimethylgermyl groups, in combination with a stabilizing dimethylamido group, were pursued as potential precursors for ALD of elemental boron. This ALD process would employ a boron trihalide (BX3; X = F, Cl, Br, I) co-reactant, exploiting the thermodynamically favourable formation of tetrel-halide bonds as a driving force. This work required multistep syntheses of alkali metal silyl reagents, {(Me3Si)3Si}Li(THF)2 (3-1) and tBu3SiNa(THF)n (3-2), and previously un-isolated [Me3GeLi(THF)2]2 (3-3), and their reactions with B(NMe2)Cl2 (3-4). The boranes {(Me3Si)3Si}2B(NMe2) (3-8) and (tBu3Si)(Me3Ge)B(NMe2) (3-12) were successfully synthesized, spectroscopically and crystallographically characterized, and assessed for their suitability as precursor molecules for boron ALD. Unfortunately, deposition attempts on SiO2/Si using 3-8 and BCl3 led to minor film growth (GPC = 0.01 Å). However, the enhanced volatility and solution-state reactivity of 3-12 in comparison to 3-8 makes it a promising precursor candidate for future ALD reactor studies. Attempts to synthesize bis(trimethylgermyl)(dimethylamido)borane from the 2:1 reaction of 3-3 with 3-4 resulted in the formation of a lithium trigermylamidoborate, {(Me3Ge)3B(NMe2)}Li(THF)2 (3-13). ALD can give rise to uniquely uniform and conformal ultra-thin films, but voids often remain after attempted filling of narrow high-aspect-ratio trenches. To achieve void-free trench-filling, ALD (or CVD; chemical vapour deposition) methods which deposit a flowable material are desirable, and this initially-deposited material can be converted to the target material (e.g. a metal oxide) by post-deposition annealing, or potentially at the deposition temperature on a longer timescale than flowable behaviour. In this work, a new HfO2 ALD process was developed using [Hf(NMeEt)4] in combination with β- hydroxyisovaleric acid (IVA; CMe2(OH)CH2CO2H) that introduces the potential for flowability. Self-limiting growth was observed at 100, 250, and 300 °C, with a GPC of 1.5- 2.2 Å on planar SiO2 substrates. Films deposited at 100 °C consisted of amorphous HfO2 with significant carbon content (~22 at%) and <1 at% nitrogen. After annealing at 400 °C in vacuo for 1 hour, the films were composed of amorphous HfO2 with low (<1 at%) carbon content. The co-reactant in this work, β-hydroxyisovaleric acid, was chosen with the following criteria in mind: Firstly, the carboxylic acid group may be sufficiently acidic to cleave linkages between chemisorbed hafnium species and the surface, generating flowable non-surface-tethered hafnium carboxylate species (with low volatility, so that they are not lost from the surface). Secondly, the hydroxyl groups of the ligands can potentially serve as reactive sites for the hafnium precursor delivered in the next pulse. Thirdly, fairly low-energy pathways should exist for deprotonated IVA ligands to decompose to generate oxide or hydroxide ligands with release of volatile by-products, such as CO2 and isobutene, or acetone and ketene. Experiments to gain insight into the nature of reactivity between [Hf(NMeEt)4] and IVA and a structurally similar carboxylic acid are described. These include (a) solution-state reactions between [Hf(NMeEt)4] and IVA or pivalic acid (tBuCO2H), with formation of [H2NMeEt]2[Hf(κ2-O2CCH2CMe2OH)2(κ2- OC(O)CH2CMe2O)2] (4-1) and [Hf5(μ3-O)4(κ2-O2CtBu)4(μ-O2CtBu)8] (4-2), (b) attempted ALD using pivalic acid (which lacks a hydroxyl group) in place of IVA, and (c) roomtemperature solution reactions between [Hf(NMeEt)4] and 4 equiv. of IVA to form 4-1, followed by removal of volatiles, heating at 200 °C, and volatile/soluble product analysis by NMR spectroscopy and GC-MS headspace analysis. Compounds 4-1 and 4-2 were isolated and crystallographically characterized. Heteroleptic zirconium(IV) complexes were designed, synthesized, spectroscopically and crystallographically characterized, and assessed as potential precursor molecules to enable flowable ZrO2 ALD. The envisaged process would operate via the deposition of oligomeric, one-dimensional chains that, if grown untethered on a functionalized substrate, could potentially flow to the bottoms of trenches. Reaction of one equivalent of H2(acen), H2(cis-Cyacen) or H2(trans-Cyacen) with [Zr(CH2SiMe3)4] at room temperature afforded [Zr(acen)(CH2SiMe3)2] (5-1), [Zr(cis-Cyacen)(CH2SiMe3)2] (5-2) or [Zr(trans-Cyacen)(CH2SiMe3)2] (5-3), respectively (acen = C2H4(NCMeCHC(O)Me)2; Cyacen = 1,2-C6H10(NCMeCHC(O)Me)2). These alkyl compounds are trigonal prismatic in the solid state, and whereas 5-1 and 5-3 decomposed without sublimation above 120 °C (5-10 mTorr), 5-2 sublimed in >95% yield at 85 °C (5-10 mTorr). However, heating solid 5-2 at 88 °C under static argon for 24 hours resulted in extensive decomposition to afford H2(cis-Cyacen) and SiMe4 as the soluble products. Compound 5-2 reacted cleanly with two equivalents of tBuOH to afford [Zr(cis-Cyacen)(OtBu)2] (5-4), but excess tBuOH caused both SiMe4 and H2(cis-Cyacen) elimination. The 1:1 reaction of H2(acen) with [Zr(NMeEt)4] did not proceed cleanly, and 8-coordinate [Zr(acen)2] (5-5) was identified as a by-product; this complex was isolated from the 2:1 reaction. A zirconium amido complex, [Zr(acen)(NMeEt)2] (5-6) was accessed via the reaction of 1 with two equiv. or excess HNMeEt, but decomposed readily in solution at room temperature. More sterically hindered [Zr(acen){N(SiMe3)2}2] (5-7) was synthesized via the reaction of [Zr(acen)Cl2] with two equivalents of Li{N(SiMe3)2}, but was also thermally unstable as a solid and in solution at room temperature. Compounds 5-1 to 5-3, 5-5 and 5-7 were crystallographically characterized.
ATOMIC LAYER DEPOSITION OF NONMETALS AND METAL OXIDES
Keywords: Atomic Layer Deposition; Antimony; Boron; Hafnium; Zirconium; Silyl; Germyl; Carboxylic Acid; Acen